2012
DOI: 10.1017/s1368980012000614
|View full text |Cite
|
Sign up to set email alerts
|

Egg consumption and the risk of type 2 diabetes mellitus: a case–control study

Abstract: Objective: Type 2 diabetes mellitus appears to involve an interaction between susceptible genetic backgrounds and environmental factors including highly calorific diets. As it is important to identify modifiable risk factors that may help reduce the risk of type 2 diabetes mellitus, the aim of the present study was to determine the association between egg consumption and the risk of type 2 diabetes mellitus. Design: A specifically designed questionnaire was used to collect information on possible risk factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 22 publications
2
30
0
4
Order By: Relevance
“…Intervention studies that controlled for many of these confounding factors, and especially the intake of saturated fat, found, in the main, no significant effect of egg intake on serum LDL-cholesterol (33)(34)(35)(36)(37)(38) , but clear evidence of a dose-response relationship between dietary cholesterol and serum LDL-cholesterol (34) , and considerable variation in the response of serum LDL-cholesterol in both men and women (35,36) . Cross-sectional and prospective cohort studies and meta-analyses, have also reported associations between egg intake and an increased incidence of diabetes, and elevated CVD risk in diabetes (12)(13)(14)(15)(16) .…”
Section: Egg: Nutrient Compositionmentioning
confidence: 97%
See 2 more Smart Citations
“…Intervention studies that controlled for many of these confounding factors, and especially the intake of saturated fat, found, in the main, no significant effect of egg intake on serum LDL-cholesterol (33)(34)(35)(36)(37)(38) , but clear evidence of a dose-response relationship between dietary cholesterol and serum LDL-cholesterol (34) , and considerable variation in the response of serum LDL-cholesterol in both men and women (35,36) . Cross-sectional and prospective cohort studies and meta-analyses, have also reported associations between egg intake and an increased incidence of diabetes, and elevated CVD risk in diabetes (12)(13)(14)(15)(16) .…”
Section: Egg: Nutrient Compositionmentioning
confidence: 97%
“…Evidence for associations between egg intake and increased incidence of diabetes in meta-analyses of prospective cohort studies has been inconsistent, some of which support associations (12)(13)(14)(15)(16) , while others do not (17)(18)(19)(20) . Egg intake is a well known marker for the intake of dietary fat and energy, both of which can contribute to an increase in body weight and risk of developing diabetes.…”
Section: Eggs Intake Incidence Of Diabetes and Increased Cvd Risk Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Some have shown that egg consumption did influence the blood cholesterol level but did not increase the risk of CVD in healthy people. Meanwhile, other studies reported that high dietary cholesterol intake due to egg consumption is a risk factor for CVD and diabetes [180, 194, 197, 199, 201204]. The results of epidemiological studies and human intervention studies on the relationship of dietary egg intake and CVD risks are summarized in Table 3.…”
Section: The Relationship Between Egg Intake and Cvd Risksmentioning
confidence: 99%
“…These studies also showed that diabetic people are more vulnerable to CVD after egg consumption [13, 208], with a doubling of coronary risk with an egg per day in US population [12, 13], and 5-fold risk in Greece population [213]. Meanwhile, some studies found that high egg consumption increased the risk of gestational diabetes mellitus [214], insulin resistance [215], and the risk of diabetes [202204]. Therefore, the effect of egg consumption on CVD might be mediated by diabetes.…”
Section: The Relationship Between Egg Intake and Cvd Risksmentioning
confidence: 99%